Effect of a Financial Incentive for Colorectal Cancer Screening Adherence on the Appropriateness of Colonoscopy Orders. (May 2017) - Morland, Thomas B.; Synnestvedt, Marie; Honeywell, Steven; Yang, Feifei; Armstrong, Katrina; Guerra, Carmen
Performance incentives for preventive care may encourage inappropriate testing, such as cancer screening for patients with short life expectancies. Defining screening colonoscopies for patients with a >50% 4-year mortality risk as inappropriate, the authors performed a pre-post analysis assessing the effect of introducing a cancer screening incentive on the proportion of screening colonoscopy orders that were inappropriate. Among 2078 orders placed by 23 attending physicians in 4 academic general internal medicine practices, only 0.6% (n = 6/1057) of screening colonoscopy orders in the preintervention period and 0.6% (n = 6/1021) of screening colonoscopy orders in the postintervention period were deemed "inappropriate." This study found no evidence that the incentive led to an increase in inappropriate screening colonoscopy orders.